Temporal trends and clinical characteristics associated with pregnancy-related acute kidney injury in England: a population-based cohort studyAJOG Global Reports at a Glance - Lisiane F. Leal, PhD; Kristian B. Filion, PhD; Robert W. Platt, PhD; K.S. Joseph, MD, PhD; Laura A. Magee, MD, FRCPC, MSc, FACP, FRCOG; Kate Bramham, MRCP; Anne-Marie Côté, FRCPC, CSPQ; Azar Mehrabadi, PhD (AJOG Global Reports, 2025)
Background: Previous studies have reported an increase in pregnancy-related acute kidney injury, but the underlying reasons and patient characteristics associated with this trend are incompletely understood. Objective: To describe temporal trends and identify clinical characteristics associated with pregnancy-related acute kidney injury in England. Study design: This population-based cohort study included all live birth and stillbirth pregnancies to persons aged 15 to 45 years, between 1998 and 2017, using general practitioner practices in England linked to hospitalization data. The outcomes were overall acute kidney injury, postpartum acute kidney injury, severe acute kidney injury, and pulmonary oedema. Adjusted risk ratios were estimated for each 5-year period using Poisson regression models. Results: Among 324,124 pregnancies (4.3% ≥ 40 years, 44.1% nulliparous), acute kidney injury increased from 2.9 to 11.2 per 10,000 pregnancies from 1998–2002 to 2013–2017. Severe acute kidney injury increased from 15.9 to 18.5 per 100,000 pregnancies from 1998–2007 to 2008–2017, while pulmonary oedema decreased from 16 to <5 events per 100,000 pregnancies. Acute kidney injury incidence increased markedly among women with hypertensive disorders and the adjusted risk ratio (aRR) for acute kidney injury among those with hypertensive disorders (vs those without) increased from 1.7 (95% confidence interval [CI] 0.4–8.1) in 1998–2002 to 4.5 (95% CI 2.6–7.7) in 2013 to 2017. There was no notable change in postpartum acute kidney injury among those with postpartum hemorrhage and the aRR for the association of postpartum hemorrhage with acute kidney injury decreased from 18.4 (95% CI 4.3–79.0) in 1998–2002 to 2.5 (95% CI 0.9–6.1) in 2013 to 2017. Few (<5) cases of acute kidney injury occurred among pregnancies with sepsis. Conclusions: There was a marked rise in pregnancy-related acute kidney injury, particularly in last 5 years of the study. The steady rise among those with hypertensive disorders suggests ongoing vigilance is required to ensure optimal care. An investigation of other potential causes or changes in case ascertainment is also warranted given the rise in acute kidney injury among those without hypertensive disorders of pregnancy.